Agrobacterium-mediated transformation of Cryptocoryne willisii with gus and mgfp 5 reporter genes / Wong Sher Ming - Wong, Sher Ming (2010)
In this study, a simple method using Murashige and Skoog basal medium (1962) supplemented with 6-BA alone was developed for direct multiple shoots induction from shoot base culture of C. willisii. Shoots proliferation and elongation were achieved on a single medium without the need of subculturing. The optimum concentration of 6-BA for direct shoots regeneration of C. willisii was investigated. It was found to be 6 mg/ L. Optimum media was then used for regenerate and propagate of transformed C. willisii. On the other hand, ransformation of C. willisii with Agrobacterium tumefaciens strain LBA4404 harbouring pCAMBIA1304 was performed. Effects on different infection times (2, 4, 6, 8, 10 mins) and co-cultivation periods (1, 2, 3, 4 days) were assessed. Analysis of β-glucuronidase (GUS) reporter gene expression through fluorometric assay revealed that the highest transformation rate (582.09 ± 84.30 pmol 4MU/mg/min) can be achieved with 6 mins of infection and one day of co-cultivation with A. tumefaciens LBA4404 harbouring pCAMBIA1304. Green fluorescent proteins (GFP) reporter genes expression was visualized under ultraviolet light. Transformed explants appeared fluorescent green under UV excitation. Plantlets of C. willisii showed positive result in fluorescent assessment were then subjected to molecular analysis. Polymerase Chain Reaction (PCR) analysis was applied to confirm the presence of mgfp5 gene in individual putative transformed C. willisii. Integration of the gene in the genome C. willisii was evidenced via Southern hybridization analysis.